Antioxidant Aryl-Substituted Phthalan Derivatives Produced by Endophytic Fungus Cytospora rhizophorae - Liu, Hongxin; Liu, Zhaoming; Zhang, Yanjiang; Chen, Yuchan; Wang, Huan; Tan, Haibo; Zhang, Weimin (Frontiers in Chemistry, 2022)
Six new phthalan derivatives cytorhizophins D-I (1-6) as well as two known derivatives cytorhizophin C and pestacin were isolated from Cytospora rhizophorae. Among them, cytorhizophins D-E (1-2) and F-G (3-4) were two pairs of diastereoisomers, all of them featuring a novel 1-phenyl-1,3-dihydroisobenzofuran scaffold with a highly oxygenated O-linked isopentenyl unit; whereas cytorhizophins H-I (5-6) represent the first examples of phthalide family with fascinating 6/6/6/5 tetracyclic ring system fusing as unprecedented furo[4,3,2-kl]xanthen-2(10bH)-one skeleton. Their structures were fully characterized on the basis of extensive spectroscopic analysis, with the partial absolute configurations of 1-6 determined by electronic circular dichroism (ECD) calculations. Compounds 1-4 showed remarkable antioxidant activities with EC50 values ranging from 5.86 to 26.80 μmol/L, which are better than that of the positive control ascorbic acid (EC50 of 25.53 μmol/L).